Main-chain supramolecular block copolymers - Yang, Si Kyung; Ambade, Ashootosh V.; Weck, Marcus (Chemical Society Reviews, 2011)
Block copolymers are key building blocks for a variety of applications ranging from electronic devices to drug delivery. The material properties of block copolymers can be tuned and potentially improved by introducing noncovalent interactions in place of covalent linkages between polymeric blocks resulting in the formation of supramolecular block copolymers. Such materials combine the microphase separation behavior inherent to block copolymers with the responsiveness of supramolecular materials thereby affording dynamic and reversible materials. This tutorial review covers recent advances in main-chain supramolecular block copolymers and describes the design principles, synthetic approaches, advantages, and potential applications.